Episodes of high tropospheric ozone reduce nodulation, seed production and quality in soybean (Glycine max (L.) merr.) on low fertility soils - Biancari, Lucio; Cerrota, Clara; Menéndez, Analía; Gundel, Pedro Emilio; Martínez Ghersa, María Alejandra (My University, 2021)
Driven by human activities, air pollution and soil degradation are threatening food production systems. Rising ozone in the troposphere can affect several physiological processes in plants and their interaction with symbiotic microorganisms. Plant responses to ozone may depend on both soil fertility and the ontogenetic stage in which they are exposed. In this work, we studied the effects of ozone episodes and soil fertility on soybean plants. We analysed soybean plant responses in the production of aboveground and belowground biomass, structural and functional attributes of rhizobia, and seed production and quality. The experiment was performed with plants grown in two substrates with different fertility (commercial soil, and soil diluted (50%, v/v) with sand). Plants were exposed to acute episodes of ozone during vegetative and reproductive stages. We observed that ozone significantly reduced belowground biomass (z25%), nodule biomass (z30%), and biological nitrogen fixation (z21%). Plants exposed to ozone during reproductive stage growing in soil with reduced fertility had lower seed production (z10% lower) and seed protein (z12% lower). These responses on yield and quality can be explained by the observed changes in belowground biomass and nitrogen fixation. The negative impact of ozone on the symbiotic interaction with rhizobia, seed production and quality in soybean plants were greater in soils with reduced fertility. Our results indicate that food security could be at risk in the future if trends in ozone concentration and soil degradation processes continue to increase.
Keywords: Ciencias agrícolas::Agricultura, Silvicultura y Pesca